2018
DOI: 10.1007/s00423-018-1697-7
|View full text |Cite
|
Sign up to set email alerts
|

Karydakis flap reconstruction versus Limberg flap transposition for pilonidal sinus disease: a meta-analysis of randomized controlled trials

Abstract: Recurrence rates of PSD were found to be similar in both study groups. Post-operative seroma rate was significantly higher in the KF group. The meta-analysis did not indicate any further statistically significant differences between the two surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
3
28
0
3
Order By: Relevance
“…Looking to various meta-analyses involving randomized controlled studies comparing KF and LF methods, rates of se- roma have been found significantly higher with KF technique. No significant difference was found in terms of recurrence rates and other variables (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Looking to various meta-analyses involving randomized controlled studies comparing KF and LF methods, rates of se- roma have been found significantly higher with KF technique. No significant difference was found in terms of recurrence rates and other variables (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 74%
“…In the LF group, 3 (5.9%) developed seroma in the wound site, 1 (2%) hematoma in the wound site, 1 (2%) wound site infection and 1 (2%) dehiscence of incision when skin sutures were removed. During follow up, recurrence was found as 5.9% (n= 3) in the LF group with a mean duration to recurrence as 22 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months. Duration to recurrence was statistically shorter in the KF group compared to the LF group (p= 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…KF required shorter operating time in all studies. Most of the studies report similar time to return to work in both arms [29].…”
Section: Excisional Proceduresmentioning
confidence: 91%
“…However, there was a shorter time to return to work seen with the Karydakis flap (Standardised mean difference −0.18, 95% CI −0.035 to −0.008). Karydakis and Limberg flaps again appeared to be comparable in a more recent meta‐analysis of 8 RCTs (6 single‐centre and 2 multi‐centre trials) that directly compared the two types of flap, including a total of 1121 patients (Karydakis n = 554 and Limberg n = 567) . There was no significant difference between the two flaps in the primary outcome of the recurrence rate (OR 1.07, 95% CI 0.59‐1.92; P = 0.83), although follow‐up duration varied from 15.5 to 33.3 months.…”
Section: Chronic Disease Treatmentsmentioning
confidence: 94%